Experts on Resistance to Reorganization of Structure and Technologies of Urban Mobility Provision in Russia: Challenges, Reasons, Solutions and Prospects - Artur I. Petrov; Dmitrii A. Zakharov; Daria A. Petrova (Automotive Experiences, 2023)
In 2022 a lot has changed in the Russian transport system. Today the urban transport systems of Russian cities are staying at the bifurcation point ”“ they are awaiting serious changes. Therefore, it was interesting to investigate expert opinions of specialists on the prospects of the development of urban mobility provision technologies in Russia and possible changes in the current structure of citizens’ transportation approaches. The paper gives results of the research of opinions of transport market specialists on the issues of the probability of the shift of the current paradigm of transport services in Tyumen (a large Russian city with a population of 828.5 thousand people) and the necessity of reorganization of the structure and technologies of urban mobility provision due to the withdrawal of foreign automakers from the Russian market. The article presents the comparison of opinions between Tyumen professionals in the transport market and ordinary Russian citizens. The main conclusion of the research considers the serious resistance of the public environment to the expected reorganization of the structure and technologies of urban mobility provision in Russia.